A kind of high-efficiency thermal conductive antistatic EVA material and preparation method thereof

By adding modified composite particles and carbon fibers to the EVA material, the conductive and thermal conductivity of the modified composite particles and the self-assembly of quaternary ammonium chitosan are solved, and the problem of insufficient thermal conductivity, conductivity and antibacterial properties of EVA materials are used to solve the problem of insufficient thermal conductivity, conductivity and antibacterial properties of EVA materials. , achieving efficient thermal conduction and anti-static effect.

CN118772525BActive Publication Date: 2025-02-07GUANGDONG BOSHIDA NEW MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411274549.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-12
Publication Date
2025-02-07
Estimated Expiration
2044-09-12
Patent Text Reader

Abstract

The present application relates to the field of ethylene copolymer materials, and specifically discloses a highly efficient heat-conductive antistatic EVA material and a preparation method thereof. The material includes the following components in parts by weight: 100-120 parts of ethylene-vinyl acetate copolymer, 20-30 parts of modified composite particles, 10-15 parts of carbon fiber, 0.5-1 parts of antioxidant, and 0.6-1.2 parts of lubricant; the modified composite particles are modified by silane coupling agent modified carbon black and silane coupling agent modified aluminum nitride to modify carboxyl carbon nanotubes at the same time, and then modified by quaternary ammonium salt chitosan. The material of the present application has excellent thermal and electrical conductivity, and also has certain antibacterial properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of ethylene copolymer materials, and more specifically, to a highly efficient thermally conductive antistatic EVA material and a preparation method thereof. Background Art

[0002] Ethylene-vinyl acetate copolymer, or EVA, is a general-purpose plastic with excellent toughness and impact resistance, and is widely used in agriculture, packaging, construction, wires and cables, etc. As the application of EVA plastics becomes increasingly widespread, refined, and safe, the static electricity effect of the products, the insecurity caused by low thermal conductivity, and poor antibacterial properties limit the scope of use of the material.

[0003] In the prior art, the conductivity is usually improved by adding conductive fillers. Compared with antistatic agents, conductive fillers can achieve a lasting effect of preventing static electricity. The thermal conductivity of the material can be increased by adding thermal conductive fillers. The conductivity and thermal conductivity are improved by adding non-insulating fillers such as carbon black, but its thermal conductivity still cannot meet the requirements of use. Carbon nanotubes are a kind of high thermal conductivity and high electrical conductivity filler, which can improve the thermal conductivity and electrical conductivity of the material. However, carbon nanotubes are expensive and costly. In addition, when used in large quantities, carbon nanotubes have poor compatibility in EVA, are easy to agglomerate, have poor dispersibility, and are also easy to affect the mechanical properties of the material. More post-processing is needed to solve the problem of large-scale use. Therefore, how to obtain an EVA material with high thermal conductivity, electrical conductivity and antibacterial effect is an urgent problem to be solved. Summary of the invention

[0004] In order to solve the problems of poor thermal conductivity, electrical conductivity and antibacterial properties of EVA materials, the present application provides a high-efficiency thermally conductive and antistatic EVA material and a preparation method thereof.

[0005] In a first aspect, the present application provides a highly efficient thermally conductive antistatic EVA material, comprising the following components in parts by weight:

[0006] 100-120 parts of ethylene-vinyl acetate copolymer,

[0007] 20-30 parts of modified composite particles,

[0008] 10-15 parts of carbon fiber,

[0009] Antioxidant 0.5-1 part,

[0010] Lubricant 0.6-1.2 parts,

[0011] The modified composite particles are obtained by modifying carboxyl carbon nanotubes by modifying carbon black with a silane coupling agent and aluminum nitride with a silane coupling agent, and then modifying them with quaternary ammonium salt chitosan.

[0012] Carbon black has good electrical conductivity, but the thermal conductivity of carbon black added alone is far from what is expected, so the inventors considered adding aluminum nitride, which has excellent thermal conductivity. Adding it to the material can greatly improve the thermal conductivity of the EVA material. By modifying the silane coupling agent, the compatibility of carbon black and aluminum nitride in the EVA material is improved, and the electrical and thermal conductivity can be better exerted. Carbon nanotubes have excellent thermal and electrical conductivity. Grafting carbon black and aluminum nitride to carbon nanotubes through silane coupling agents is conducive to forming thermal and electrical conduction paths, improving the thermal and electrical conductivity of the material.

[0013] Carbon black and aluminum nitride are added to the material at the same time, and aluminum nitride has insulation, and the random dispersion of carbon black and aluminum nitride in the resin affects the construction of the conductive path, making the conductivity poor. The inventor makes carbon black and aluminum nitride arranged regularly in the resin system to a certain extent by grafting carbon black and aluminum nitride on carboxyl carbon nanotubes, reducing the influence of aluminum nitride on the conductive path of carbon black and carbon nanotubes, and in addition, when preparing composite particles, further adding quaternary ammonium salt chitosan also gives the material certain antibacterial property. Quaternary ammonium salt chitosan has excellent antibacterial property and antistatic property, and its antibacterial effect is better than chitosan, therefore, quaternary ammonium salt chitosan is added to the material to give antibacterial property. More importantly, the inventors found that adding quaternary ammonium chitosan when preparing composite particles is beneficial to the improvement of the electrical and thermal conductivity of the material. The inventors believe that this may be due to the fact that quaternary ammonium chitosan is positively charged, and carboxyl carbon nanotubes also include some carboxyl groups after grafting, and carboxyl groups are negatively charged and can achieve self-assembly through electrostatic self-assembly, so that the quaternary ammonium chitosan and carbon nanotubes form a force, effectively controlling the arrangement of carbon black and aluminum nitride grafted on the surface of carbon nanotubes, and greatly reducing the influence of aluminum nitride on the construction of carbon nanotube and carbon black conductive paths. As a result, good thermal and electrical paths are constructed in the system, improving the thermal and electrical conductivity of the material.

[0014] Carbon fiber also has excellent thermal and electrical conductivity. Adding carbon fiber to the material can improve the electrical and thermal conductivity. The inventors have found through experiments that adding modified composite particles and carbon fibers to the material together has better thermal and electrical conductivity than using modified composite particles or carbon fibers alone. This may be because when carbon fiber is added to the material, due to grafting and self-assembly, carbon black and aluminum nitride are arranged in a regular pattern, and an excellent conductive path is constructed through carbon nanotubes, carbon black, and carbon fibers, while carbon nanotubes, aluminum nitride, and carbon fibers construct a good thermal conductive path in the system. Therefore, the structure of the modified composite particles is conducive to the construction of conductive and thermal conductive paths, reducing the influence of insulating particles, thereby improving the thermal and electrical conductivity of the material.

[0015] In a specific embodiment, the method for preparing the modified composite particles comprises the following steps:

[0016] S1: adding carbon black and aluminum nitride into a silane coupling agent solution to obtain modified carbon black and modified aluminum nitride;

[0017] S2: adding the modified carbon black, modified aluminum nitride and carboxyl carbon nanotubes in S1 into an organic solvent, heating the mixture for reaction, and removing the solvent to obtain composite particles;

[0018] S3: dissolving quaternary ammonium chitosan in water to obtain a quaternary ammonium chitosan solution, dispersing the composite particles of S2 in water to obtain a composite particle suspension, dropping the composite particle suspension into the quaternary ammonium chitosan solution, and post-treating to obtain modified composite particles.

[0019] Carbon black and aluminum nitride are modified by aminosilane and conventional hydrolyzed silane. The hydrolyzed hydroxyl groups react with the hydroxyl groups on the surface of the particles to achieve modification, which can improve the compatibility of the particles in the resin material. The surface amino groups react with the carboxyl groups in the carboxyl carbon nanotubes to graft the carbon black and aluminum nitride to the carbon nanotubes. The modified composite particles are then prepared through the self-assembly of quaternary ammonium chitosan and carboxyl carbon nanotubes.

[0020] In a specific embodiment, the mass ratio of the quaternary ammonium salt chitosan and the composite particles in S3 is (2-4):1.

[0021] When preparing particles, preferably, the mass ratio of quaternary ammonium salt chitosan to composite particles is selected to be (2-4):1. It is found through experiments that the modified composite particles are prepared by adding raw materials in the above ratio, and the conductive performance is best when the materials are added. This may be because if the amount of quaternary ammonium salt chitosan added is small, the control of carbon black and aluminum nitride grafted on the surface of carbon fiber is reduced, and the random arrangement of aluminum nitride affects the construction of the conductive path, so that the conductive performance is reduced. If the amount of quaternary ammonium salt chitosan added is large, there are many positive electrons in the system. Due to the repulsion of like electrons and the steric hindrance of quaternary ammonium salt chitosan, it is not conducive to the construction of the conductive path between the modified composite particles and the carbon fiber, and the conductive performance is reduced.

[0022] In a specific embodiment, the silane coupling agent described in S1 is one or more of γ-aminopropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, and aminoethylaminoethylaminopropyltrimethoxysilane.

[0023] Preferably, the silane coupling agent described in S1 is N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane. The modification and grafting of carbon black and aluminum nitride are achieved by aminosilane modification. Among them, the modified composite particles obtained by selecting N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane for modification have the best material conductivity. This may be because the structural formula of γ-aminopropyltrimethoxysilane is H2NCH2CH2CH2Si(OCH3)3; the structural formula of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane is H2NCH2CH2NHCH2CH2CH2 Si(OCH3)3; The structural formula of aminoethylaminoethylaminopropyltrimethoxysilane is H2NCH2CH2NHCH2CH2NHCH2CH2CH2Si(OCH3)3; Among them, the chain length of silane is shorter, and the construction of conductive and thermal conductive paths is slightly worse, but the chain length of silane is too long, the particle arrangement tends to be uncontrollable, and it is easy to cause the insulating particles to affect the construction of the conductive path. Therefore, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane is preferred for modification.

[0024] In a specific embodiment, the carboxyl carbon nanotubes are carboxylated multi-walled carbon nanotubes with a diameter of 40-60 nm and a length of 8-20 μm.

[0025] In a specific embodiment, the carbon fiber is a nanocarbon fiber with a diameter of 150-200 nanometers and a length of 10-20 μm.

[0026] By specifically selecting carbon nanotubes and carbon fibers, the thermal and electrical conductivity can be improved. If the length of carbon nanotubes is too short, it is not conducive to the preparation of composite particles and the construction of thermal and electrical conduction paths. If the length of carbon fibers is too short, it is not conducive to the construction of electrical and thermal conduction paths.

[0027] In a specific embodiment, the antioxidant is one or two of antioxidant 1010, antioxidant 1076, and antioxidant 168.

[0028] In a specific embodiment, the lubricant is one or both of polyethylene wax and low molecular weight polypropylene.

[0029] In the material of the present application, functional additives such as antioxidants, lubricants, plasticizers, etc. may be added according to performance requirements to improve the preparation quality of the material.

[0030] On the other hand, the present application provides a method for preparing a high-efficiency thermally conductive and anti-static EVA material, comprising the following steps: melting ethylene-vinyl acetate copolymer, adding the remaining components of the formula, heating, extruding and granulating to obtain a high-efficiency thermally conductive and anti-static EVA material.

[0031] The EVA material is prepared by melt extrusion. The components of the present invention are simple, the preparation process is not complicated, and a highly efficient thermal and electrical conductive material is prepared.

[0032] This application has at least the following beneficial effects:

[0033] 1. The present application prepares composite materials by adding modified composite particles and carbon fiber to EVA to improve thermal conductivity and electrical conductivity, and endows the material with certain antibacterial properties. When preparing modified composite particles, carbon black and aluminum nitride are grafted to carbon nanotubes through silane coupling agents, which is conducive to forming thermal and electrical conductivity paths. Further addition of quaternary ammonium salt chitosan gives the material certain antibacterial properties, and greatly improves the electrical conductivity and thermal conductivity of the material. This may be due to the fact that quaternary ammonium salt chitosan and carboxyl carbon nanotubes achieve self-assembly through electrostatic self-assembly, so that the quaternary ammonium salt chitosan and carbon nanotubes form a force, effectively controlling the arrangement of carbon black and aluminum nitride grafted on the surface of carbon nanotubes, and greatly reducing the influence of aluminum nitride on the construction of conductive paths. Thus, good thermal and electrical paths are constructed in the system, and the thermal and electrical conductivity of the material is improved. Carbon fiber is added to the material, and an excellent conductive pathway is constructed through carbon nanotubes, carbon black, and carbon fiber, while carbon nanotubes, aluminum nitride, and carbon fiber construct a good thermal conductive pathway in the system. The structure of the composite particles is conducive to the construction of the pathway, reducing the impact of insulating particles, thereby improving the thermal and electrical conductivity of the material.

[0034] 2. When preparing particles in this application, the mass ratio of quaternary ammonium salt chitosan and composite particles is selected to be (2-4): 1. The raw materials in the above ratio are added to prepare modified composite particles. When the materials are added, the electrical conductivity is the best and the thermal conductivity is maintained well.

[0035] 3. The silane coupling agent in the present application is preferably a modified composite particle obtained by using N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane coupling agent, which improves the conductive properties of the material. DETAILED DESCRIPTION

[0036] The present application is further described in detail below in conjunction with the examples. DuPont ELvax 420 is selected as the ethylene-vinyl acetate copolymer; the carbon fiber has a diameter of 150-200 nanometers and a length of 10-20 μm, which is a nano carbon fiber from Ke Leiming (Beijing) Technology Co., Ltd.; antioxidant 1010; the lubricant is DT WAX® W100F polyethylene wax; the carboxyl carbon nanotube has a diameter of 40-60 nm and a length of 10 μm, which is a carboxyl carbon black from Suzhou Beike Nanotechnology; the carbon black is T250 from Ruiyat (Tianjin) Chemical; the aluminum nitride is the ultrafine aluminum nitride from Hebei Teng Bimetallic Materials Co., Ltd., with a mesh size of 15,000 mesh. The quaternary ammonium salt chitosan is hydroxypropyltrimethylammonium chloride chitosan from Qingdao Bozhi Huili Biotechnology Co., Ltd. The experimental reagents in the examples or comparative examples, unless otherwise specified, are all conventional commercial brands or obtained through conventional preparation processes.

[0037] Preparation Example 1:

[0038] 200 g of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane coupling agent was dissolved in 1 kg of ethanol aqueous solution (volume ratio 1:1) to prepare a silane coupling agent solution, 20 g of carbon black was added to the above solution, heated to 90°C and refluxed for reaction for 40 min, centrifuged after the reaction, washed with water twice, and dried in a 60°C oven to obtain silane coupling agent modified carbon black;

[0039] 35 g of aluminum nitride was added to the silane coupling agent solution prepared above, heated to 85° C. and refluxed for reaction for 1.5 h. After the reaction, the mixture was centrifuged, washed with water twice, and dried in an oven at 60° C. to obtain aluminum nitride modified with a silane coupling agent.

[0040] 20 g of the above-mentioned silane coupling agent modified carbon black, 20 g of modified aluminum nitride, and 15 g of carboxyl carbon nanotubes were added to 250 mL of DMF, reacted at 95° C. for 3.5 h, the solvent was removed, washed twice with ethanol and twice with water, and dried to obtain composite particles;

[0041] 3 g of quaternary ammonium chitosan was dissolved in 3 L of water and stirred to obtain a quaternary ammonium chitosan solution. 1 g of the above composite particles was dispersed in 200 mL of deionized water to obtain a composite particle suspension. The above composite particle suspension was added dropwise to the above quaternary ammonium chitosan solution, stirred evenly, allowed to stand for 1 hour, centrifuged, and dried to obtain modified composite particles.

[0042] Preparation Example 2:

[0043] 200 g of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane coupling agent was dissolved in 1 kg of ethanol aqueous solution (volume ratio 1:1) to prepare a silane coupling agent solution, 20 g of carbon black was added to the above solution, heated to 90°C and refluxed for reaction for 40 min, centrifuged after the reaction, washed with water twice, and dried in a 60°C oven to obtain silane coupling agent modified carbon black;

[0044] 35 g of aluminum nitride was added to the silane coupling agent solution prepared above, heated to 85° C. and refluxed for reaction for 1.5 h. After the reaction, the mixture was centrifuged, washed with water twice, and dried in an oven at 60° C. to obtain aluminum nitride modified with a silane coupling agent.

[0045] 20 g of the above-mentioned silane coupling agent modified carbon black, 20 g of modified aluminum nitride, and 15 g of carboxyl carbon nanotubes were added to 250 mL of DMF, reacted at 95° C. for 3.5 h, the solvent was removed, washed twice with ethanol and twice with water, and dried to obtain composite particles;

[0046] 1 g of quaternary ammonium chitosan was dissolved in 3 L of water and stirred to obtain a quaternary ammonium chitosan solution. 1 g of the above composite particles was dispersed in 200 mL of deionized water to obtain a composite particle suspension. The above composite particle suspension was added dropwise to the above quaternary ammonium chitosan solution, stirred evenly, allowed to stand for 1 hour, centrifuged, and dried to obtain modified composite particles.

[0047] Preparation Example 3:

[0048] 200 g of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane coupling agent was dissolved in 1 kg of ethanol aqueous solution (volume ratio 1:1) to prepare a silane coupling agent solution, 20 g of carbon black was added to the above solution, heated to 90°C and refluxed for reaction for 40 min, centrifuged after the reaction, washed with water twice, and dried in a 60°C oven to obtain silane coupling agent modified carbon black;

[0049] 35 g of aluminum nitride was added to the silane coupling agent solution prepared above, heated to 85° C. and refluxed for reaction for 1.5 h. After the reaction, the mixture was centrifuged, washed with water twice, and dried in an oven at 60° C. to obtain aluminum nitride modified with a silane coupling agent.

[0050] 20 g of the above-mentioned silane coupling agent modified carbon black, 20 g of modified aluminum nitride, and 15 g of carboxyl carbon nanotubes were added to 250 mL of DMF, reacted at 95° C. for 3.5 h, the solvent was removed, washed twice with ethanol and twice with water, and dried to obtain composite particles;

[0051] 5 g of quaternary ammonium chitosan was dissolved in 3 L of water and stirred to obtain a quaternary ammonium chitosan solution. 1 g of the above composite particles was dispersed in 200 mL of deionized water to obtain a composite particle suspension. The above composite particle suspension was added dropwise to the above quaternary ammonium chitosan solution, stirred evenly, allowed to stand for 1 hour, centrifuged, and dried to obtain modified composite particles.

[0052] Preparation Example 4:

[0053] 200 g of γ-aminopropyltrimethoxysilane was dissolved in 1 kg of ethanol aqueous solution (volume ratio 1:1) to prepare a silane coupling agent solution, 20 g of carbon black was added to the above solution, heated to 90°C and refluxed for reaction for 40 min, centrifuged after the reaction, washed with water twice, and dried in a 60°C oven to obtain silane coupling agent modified carbon black;

[0054] 35 g of aluminum nitride was added to the silane coupling agent solution prepared above, heated to 85° C. and refluxed for reaction for 1.5 h. After the reaction, the mixture was centrifuged, washed with water twice, and dried in an oven at 60° C. to obtain aluminum nitride modified with a silane coupling agent.

[0055] 20 g of the above-mentioned silane coupling agent modified carbon black, 20 g of modified aluminum nitride, and 15 g of carboxyl carbon nanotubes were added to 250 mL of DMF, reacted at 95° C. for 3.5 h, the solvent was removed, washed twice with ethanol and twice with water, and dried to obtain composite particles;

[0056] 3 g of quaternary ammonium chitosan was dissolved in 3 L of water and stirred to obtain a quaternary ammonium chitosan solution. 1 g of the above composite particles was dispersed in 200 mL of deionized water to obtain a composite particle suspension. The above composite particle suspension was added dropwise to the above quaternary ammonium chitosan solution, stirred evenly, allowed to stand for 1 hour, centrifuged, and dried to obtain modified composite particles.

[0057] Preparation Example 5:

[0058] Dissolve 200g of aminoethylaminoethylaminopropyltrimethoxysilane in 1kg of ethanol aqueous solution (volume ratio 1:1) to prepare a silane coupling agent solution, add 20g of carbon black to the above solution, heat to 90°C and reflux for reaction for 40min, centrifuge after reaction, wash with water twice, and dry in a 60°C oven to obtain silane coupling agent modified carbon black;

[0059] 35 g of aluminum nitride was added to the silane coupling agent solution prepared above, heated to 85° C. and refluxed for reaction for 1.5 h. After the reaction, the mixture was centrifuged, washed with water twice, and dried in an oven at 60° C. to obtain aluminum nitride modified with a silane coupling agent.

[0060] 20 g of the above-mentioned silane coupling agent modified carbon black, 20 g of modified aluminum nitride, and 15 g of carboxyl carbon nanotubes were added to 250 mL of DMF, reacted at 95° C. for 3.5 h, the solvent was removed, washed twice with ethanol and twice with water, and dried to obtain composite particles;

[0061] 3 g of quaternary ammonium chitosan was dissolved in 3 L of water and stirred to obtain a quaternary ammonium chitosan solution. 1 g of the above composite particles was dispersed in 200 mL of deionized water to obtain a composite particle suspension. The above composite particle suspension was added dropwise to the above quaternary ammonium chitosan solution, stirred evenly, allowed to stand for 1 hour, centrifuged, and dried to obtain modified composite particles.

[0062] Preparation Example 6:

[0063] 200 g of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane coupling agent was dissolved in 1 kg of ethanol aqueous solution (volume ratio 1:1) to prepare a silane coupling agent solution, 20 g of carbon black was added to the above solution, heated to 90°C and refluxed for reaction for 40 min, centrifuged after the reaction, washed with water twice, and dried in a 60°C oven to obtain silane coupling agent modified carbon black;

[0064] 35 g of aluminum nitride was added to the silane coupling agent solution prepared above, heated to 85° C. and refluxed for reaction for 1.5 h. After the reaction, the mixture was centrifuged, washed with water twice, and dried in an oven at 60° C. to obtain aluminum nitride modified with a silane coupling agent.

[0065] 20 g of the above-mentioned silane coupling agent modified carbon black, 20 g of modified aluminum nitride, and 15 g of carboxyl carbon nanotubes are blended to obtain composite particles;

[0066] Preparation Example 7:

[0067] 200 g of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane coupling agent was dissolved in 1 kg of ethanol aqueous solution (volume ratio 1:1) to prepare a silane coupling agent solution, 20 g of carbon black was added to the above solution, heated to 90°C and refluxed for reaction for 40 min, centrifuged after the reaction, washed with water twice, and dried in a 60°C oven to obtain silane coupling agent modified carbon black;

[0068] 35 g of aluminum nitride was added to the silane coupling agent solution prepared above, heated to 85° C. and refluxed for reaction for 1.5 h. After the reaction, the mixture was centrifuged, washed with water twice, and dried in an oven at 60° C. to obtain aluminum nitride modified with a silane coupling agent.

[0069] 20 g of the above-mentioned silane coupling agent modified carbon black, 20 g of modified aluminum nitride, and 15 g of carboxyl carbon nanotubes were added to 250 mL of DMF, reacted at 95° C. for 3.5 h, the solvent was removed, washed twice with ethanol and twice with water, and dried to obtain composite particles.

[0070] Example 1

[0071] 11 kg of ethylene-vinyl acetate copolymer was heated to 110° C., 2.5 kg of modified composite particles of Preparation Example 1, 1.2 kg of carbon fiber, 80 g of antioxidant, and 100 g of lubricant were added, heated to 180° C. with stirring, and extruded into granules to obtain a highly efficient thermally and electrically conductive EVA material.

[0072] Example 2

[0073] Heat 11 kg of ethylene-vinyl acetate copolymer to 110° C., add 2 kg of modified composite particles of Preparation Example 1, 1.5 kg of carbon fiber, 100 g of antioxidant, and 70 g of lubricant, heat to 180° C., stir, extrude and granulate, and obtain a high-efficiency thermally and electrically conductive EVA material.

[0074] Example 3

[0075] Heat 11 kg of ethylene-vinyl acetate copolymer to 110° C., add 3 kg of modified composite particles of Preparation Example 1, 1 kg of carbon fiber, 60 g of antioxidant, and 120 g of lubricant, heat to 180° C., stir, extrude and granulate, and obtain a high-efficiency thermally and electrically conductive EVA material.

[0076] Example 4

[0077] Heat 11 kg of ethylene-vinyl acetate copolymer to 110° C., add 2.5 kg of modified composite particles of Preparation Example 2, 1.2 kg of carbon fiber, 80 g of antioxidant, and 100 g of lubricant, heat to 180° C., stir, extrude and granulate, and obtain a highly efficient thermally and electrically conductive EVA material.

[0078] Example 5

[0079] Heat 11 kg of ethylene-vinyl acetate copolymer to 110°C, add 2.5 kg of modified composite particles of Preparation Example 3, 1.2 kg of carbon fiber, 80 g of antioxidant, and 100 g of lubricant, heat to 180°C, stir, extrude and granulate, and obtain a high-efficiency thermally and electrically conductive EVA material.

[0080] Example 6

[0081] Heat 11 kg of ethylene-vinyl acetate copolymer to 110°C, add 2.5 kg of modified composite particles of Preparation Example 4, 1.2 kg of carbon fiber, 80 g of antioxidant, and 100 g of lubricant, heat to 180°C, stir, extrude and granulate, and obtain a high-efficiency thermally and electrically conductive EVA material.

[0082] Example 7

[0083] Heat 11 kg of ethylene-vinyl acetate copolymer to 110°C, add 2.5 kg of modified composite particles of Preparation Example 5, 1.2 kg of carbon fiber, 80 g of antioxidant, and 100 g of lubricant, heat to 180°C, stir, extrude and granulate, and obtain a high-efficiency thermally and electrically conductive EVA material.

[0084] Comparative Example 1

[0085] 11 kg of ethylene-vinyl acetate copolymer was heated to 110° C., 3.7 kg of the modified composite particles of Preparation Example 1, 80 g of an antioxidant, and 100 g of a lubricant were added, and the mixture was heated to 180° C. and stirred, and extruded and granulated to obtain a highly efficient thermally and electrically conductive EVA material.

[0086] Comparative Example 2

[0087] 11 kg of ethylene-vinyl acetate copolymer was heated to 110° C., 3.7 kg of carbon fiber, 80 g of antioxidant, and 100 g of lubricant were added, and the mixture was heated to 180° C. and stirred, and extruded and granulated to obtain a highly efficient thermally and electrically conductive EVA material.

[0088] Comparative Example 3

[0089] Heat 11 kg of ethylene-vinyl acetate copolymer to 110°C, add 2.5 kg of the composite particles of Preparation Example 6, 1.2 kg of carbon fiber, 80 g of antioxidant, and 100 g of lubricant, heat to 180°C with stirring, extrude and granulate to obtain a high-efficiency thermally and electrically conductive EVA material.

[0090] Comparative Example 4

[0091] Heat 11 kg of ethylene-vinyl acetate copolymer to 110° C., add 2.5 kg of the composite particles of Preparation Example 7, 1.2 kg of carbon fiber, 80 g of antioxidant, and 100 g of lubricant, heat to 180° C. with stirring, extrude and granulate to obtain a highly efficient thermally and electrically conductive EVA material.

[0092] Performance testing:

[0093] The thermal and electrical conductivity tests were performed on the materials of Examples 1-7 and Comparative Examples 1-4. The thermal conductivity was tested according to ASTM C1113, and the volume resistivity of Examples 1-7 and Comparative Examples 1-4 was tested using a DB-4 resistance meter and a direct current-voltage method.

[0094] The test results are shown in Table 1:

[0095] Table 1 Test results of performance test

[0096] Volume resistivity at 20℃ (Ω·cm) Thermal conductivity (W / m·K) Example 1 18 3.2 Example 2 21 2.9 Example 3 20 3.1 Example 4 32 3.4 Example 5 29 2.6 Example 6 24 2.7 Example 7 26 3.3 Comparative Example 1 48 2.1 Comparative Example 2 71 1.5 Comparative Example 3 57 1.8 Comparative Example 4 42 2.4

[0097] Combining Examples 1-7 and Comparative Examples 1-4 of the present application, it can be seen that the EVA material prepared in the present application achieves excellent thermal and electrical conductivity. Combining Example 1 and Comparative Examples 1-2, it can be seen that the mixed use of modified composite particles and carbon fibers results in excellent thermal and electrical conductivity.

[0098] Combining Example 1 and Examples 4-5 of the present application, it can be seen that by preparing modified composite particles with a mass ratio of quaternary ammonium salt chitosan: composite particles of (2-4):1, the obtained material has better electrical conductivity and maintains good thermal conductivity.

[0099] It can be seen from the combination of Example 1 and Examples 6-7 of the present application that by selecting N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane for modification, the obtained material has better electrical conductivity.

[0100] In combination with Example 1 of the present application and Comparative Examples 3-4, it can be found that by grafting modified carbon black, modified aluminum nitride and carbon nanotubes, and self-assembly modification by chitosan quaternary ammonium salt, it is beneficial to construct conductive and thermal conductive pathways in the material, so that the prepared modified composite particles are added to the EVA material to achieve efficient thermal and electrical conductivity.

[0101] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A highly efficient thermally conductive antistatic EVA material, characterized in that: The composition comprises the following components in parts by weight: 100-120 parts of ethylene-vinyl acetate copolymer, 20-30 parts of modified composite particles, 10-15 parts of carbon fiber, Antioxidant 0.5-1 part, Lubricant 0.6-1.2 parts, The modified composite particles are obtained by modifying carboxyl carbon nanotubes by simultaneously modifying carbon black with a silane coupling agent and aluminum nitride with a silane coupling agent, and then modifying them with quaternary ammonium salt chitosan; The preparation method of the modified composite particles comprises the following steps: S1: adding carbon black and aluminum nitride into a silane coupling agent solution to obtain modified carbon black and modified aluminum nitride; S2: adding the modified carbon black, modified aluminum nitride and carboxyl carbon nanotubes in S1 into an organic solvent, heating the mixture for reaction, and removing the solvent to obtain composite particles; S3: dissolving quaternary ammonium salt chitosan in water to obtain a quaternary ammonium salt chitosan solution, dispersing the composite particles of S2 in water to obtain a composite particle suspension, dropping the composite particle suspension into the quaternary ammonium salt chitosan solution, and post-treating to obtain modified composite particles; The mass ratio of the quaternary ammonium salt chitosan and the composite particles in S3 is (2-4):1; The silane coupling agent described in S1 is N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane.

2. The high-efficiency thermally conductive antistatic EVA material according to claim 1, characterized in that: The carboxyl carbon nanotubes are carboxylated multi-walled carbon nanotubes with a diameter of 40-60 nm and a length of 8-20 μm.

3. The high-efficiency thermally conductive antistatic EVA material according to claim 1, characterized in that: The carbon fiber is nano carbon fiber with a diameter of 150-200 nanometers and a length of 10-20 μm.

4. The high-efficiency thermally conductive antistatic EVA material according to claim 1, characterized in that: The antioxidant is one or two of antioxidant 1010, antioxidant 1076, and antioxidant 168.

5. The high-efficiency thermally conductive antistatic EVA material according to claim 1, characterized in that: The lubricant is one or both of polyethylene wax and low molecular weight polypropylene.

6. A method for preparing a high-efficiency thermally conductive antistatic EVA material as claimed in any one of claims 1 to 5, characterized in that: The method comprises the following steps: melting ethylene-vinyl acetate copolymer, adding the remaining components of the formula, heating, extruding and granulating to obtain a high-efficiency heat-conducting and antistatic EVA material.

Citation Information

Patent Citations

  • Heat conduction and insulation plastic containing carbon nanotube filling material of special structure and preparation method thereof

    CN103554900A

  • Preparation method of compound heat conducting filler for macromolecules

    CN109679142A